Identification of two novel HLA class II alleles, HLA‐DQB1*02:139 and HLA‐DQB1*02:140, in northern Chinese individuals. (18th March 2019) - Zhou, Yunli; Zhang, Qian; Wang, Yan; Wang, Linlin; Liu, Keyao
Abstract : Two novel HLA‐DQB1 alleles, HLA‐DQB1*02:139 and HLA‐DQB1*02:140, characterized using a sequence‐based typing in northern Chinese individuals.